Cambio en la dinámica folicular en vacas cebú anéstricas sometidas a suspensión temporal de la lactancia (2000)
ABSTRACT: To evaluate the effect of the temporary suspension of lactation (TSL) on the follicular dynamics, four suckling anestric Zebu cows were selected and evaluated by ultrasound three times a week; their estrus behavior was observed twice a day and the progesterone level was determined (RM) from the 30th postpartum day. The experiment was carried out under silvopastoril conditions in a Colombian dry tropical forest zone, with 450 in of altitude, 27 °C of temperature, and IMO mm of annual rainfall. At the 148' day of postpartum period, the cows were submitted to four consecutive days of TSL, and their follicular dynamics and progesterone levels were determined. The ultrasound images were recorded on video tapes to measure the dominant follicle (OF) and the greater subordinate follicle (SF) diameter, to calculate the follicular growth rate (GR) and the interdominance interval (ID) and to determine the ovulation and the corpus luteum formation (CL). The first day of the TSL, the cows were in different states of follicular dynamics. After the TSL, two cows, that had smaller number of follicular waves (P0.001) and greater DF diameter (P<0.05), presented estrus and ovulation with CL formation and 7.5 ng/ml maximum progesterone levels compared to the other two cows that did not ovulate, which increased the OF diameter in response to TSL It is concluded that the TSL induce the estrus and ovulation in anestric Zebu cows that previously presented follicular dynamics and dominant follicles development with diameter like an ovulatory follicle, and induces an increase of the OF diameter in anestric cows that previously presented follicular dynamics with underdeveloped DE.